PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS KONSUMEN MITANA CAFÉ DI KOTA LANGSA - Tengku Putri Lindung Bulan; Tiara Sriwulan (Fakultas Ekonomi Universitas Samudra, 2021)
This study aims to determine the effect of product quality and price on consumer loyalty at Mitana Cafe in Langsa City. The number of samples in this study were 96 respondents. The data analysis method used in this study is the classical assumption test, multiple linear regression analysis and proof of the hypothesis using the coefficient of determination analysis, t test and F test. price affects consumer loyalty of Mitana Cafe in Langsa City by 24.3% and the remaining 75.7% is influenced by other variables not examined in this study. From the results of the t test it is known that product quality and price have a significant effect on consumer loyalty at Mitana Cafe in Langsa City. From the results of the F test, it is known that the product quality and price simultaneously have a significant effect on the consumer loyalty of Mitana Cafe in Langsa City.